Understanding agents of change in amenity gateways of the Greater Yellowstone region. Issue 2 (15th March 2018) - Bergstrom, Ryan D.; Harrington, Lisa M. B.
Abstract: Recognition of the Greater Yellowstone Ecosystem – lands that surround Yellowstone and Grand Teton national parks – was hoped to facilitate regional sustainability. However, with over 30 federal, tribal, state, and local agencies; thousands of private businesses and landowners; over 175 non-government organizations; and more than 16 million users annually, the region has proven difficult to manage comprehensively. It is increasingly important to understand how local stakeholders perceive control over change and the responsible agents and actors. This is particularly important in amenity gateway communities where the relationship between public lands management and local community development have become increasingly complex in recent decades. Findings suggest that not only does community proximity and dependence on Yellowstone National Park and its policies influence perceptions of the actors and agents of change, but also perceptions directly influence how gateway communities address the challenges they face.